Investigation on Heat Deflection and Thermal Conductivity of Basalt Fiber Reinforced Composites Prepared by Hand Layup Method - R. Meenakshi Reddy; S. Ravi; Pradeep Kumar Singh; H. Dineshkumar; K. Arun Bhaskar; Vallapureddy Siva Nagi Reddy; A. H. Seikh; M. H. Siddique; Ashok Nagaraj (Advances in Materials Science and Engineering)
Recent trends are shifting to the use of composite materials and their demands for making alternate materials to metals due to weight ratio, while the synthetic fiber composite also creates environmental hazards. To overcome these issues, composite materials with natural fiber reinforcement are being developed. The current work is concerned with the fabrication of composite laminates using the traditional hand layup method, with 40% reinforcement of basalt fiber mat and sawdust filler and 60% epoxy, with quantifying the thermal effects of composite laminates varying with four different weight fractions of basalt fiber and sawdust filler materials. The results revealed that maximum thermal conductance, heat deflection temperature, and coefficient of linear thermal expansion values are 0.254 W/mK, 95°C, and 2.9 × 10−5/°C, respectively, which increases sawdust filler loading resist the thermal effect compared to basalt fiber loading of hybrid composite.